Um instrumento para auxiliar o produtor na tomada de decisão quanto à data de venda da soja - SOUZA, Regina Machado de (2010)
This word aimeded to develop a friendly computational tool that, given the expectation of the producer in relation to soybean prices at a future date, help them decide whether or not it‟s worth waiting to sell their produce at that future date or sell in the current date. This work relied mainly with the System Dynamics methodology for model building and testing of Box-Jenkins to obtain the price expectations. The model also allows deriving the likely minimum price to be received by the producer in order to justify its decision to postpone its sale. We found no empirical evidence capable of sustaining the existence of a priori a better time to sell soybeans.